KEANEKARAGAMAN PALEM DI PULAU MENDANAU, BELITUNG - Deri Andayani; Eddy Nurtjahya; Himmah Rustiami (BERITA BIOLOGI, 2018)
The study of palm in the Mendanau Island, Belitung was conducted in March 2017. There were 11 palm genera consisting of 14 species: Areca catechu, Calamus densiflorus, C. erinaceus, C. scipionum, Calamus sp., Caryota mitis, Daemonorops melanochaetes, Eleiodoxa conferta, Metroxylon sagu, Oncosperma tigillarium, Orania sylvicola, Pinanga malaiana, Plectocomia elongata, and Plectocomiopsis geminiflora. Based on the study of specimens deposited at Herbarium Bogoriense (BO), there were only four species recorded from Belitung Island, namely: Calamus erinaceus, C. scipionum, Eleiodoxa conferta, and Plectocomiopsis geminiflora. One species Calamus densiflorus is a new specimen collection for BO.